How may confinement affect technicolour? - Doff, A.; Machado, F. A. [UNESP]; Natale, Adriano Antonio [UNESP] (Iop Publishing Ltd, 2012)
Confinement has been introduced into the quark gap equation, as proposed by Cornwall, as a possible solution to the problem of chiral symmetry breaking in quantum chromodynamics with dynamically massive gluons. We argue that the same mechanism can be applied for technicolour with dynamically massive technigluons. Within this approach both theories develop a hard self-energy dynamic, resulting from an effective four-fermion interaction, which does not lead to the known technicolour phenomenological problems. We outline a quite general type of technicolour model within this proposal that may naturally explain the masses of different fermion generations.